The Length of Utterances and Sentence Completeness in Preschool-Aged Children - Kusnanto, Adella Ayu Amelia Putri; Pratomo, Hafidz Triantoro Aji; Nugroho, Setyadi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Mean Length Utterance (MLU) provides essential information about language development and indicates language delay or disorders. As a child’s vocabulary increases, their language proficiency improves, resulting in a higher MLU score. It affects the completeness of their syntactic structures, allowing an assessment of their language development, particularly in the grammatical aspects of syntax and morphology. This research aims to determine the relationship between MLU and the overall completeness of syntactic structures, not just in terms of word patterns and units. It is a quantitative study using a cross-sectional method with a correlational approach. The sample consisted of 67 children in Surakarta, selected using random sampling techniques. The Pearson Product Moment correlation test results showed ρ ≤ 0.001 which is <0.05, indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. There is a significant relationship between Mean Length Utterance (MLU) and the completeness of syntactic structures. The strength of this correlation is demonstrated by a correlation coefficient (r) = 0.732**, which indicates a strong and positive correlation.